Stability-indicating spectrophotometric quantification of safinamide in the presence of its possible degradation product - Ebraam B. Kamel; Omar M El-Abassy (Scientific Reports)
Abstract In recent times, a truly exquisite pharmaceutical marvel has graced the world of medicine, known as Safinamide (SAF). This opulent creation has been specifically tailored to cater to the needs of individuals afflicted with Parkinson’s disease (PD), an esteemed neurological condition renowned for its regal ability to impede motor skills, coordination, and equilibrium. It is highly improbable that degradation products of pharmaceutical components would significantly compromise efficiency and safety of a drug during its shelf life. Pharmaceutical analysis requires a variety of stability tests to be conducted under distinct conditions. As a result, there was an increased need for the development of an analytical methodology capable of reliably separating and quantifying degradants and impurities that might be found in pharmaceuticals. In this study, we have developed two efficient and straightforward spectrophotometric methodologies for the concurrent estimation of SAF and its degradation product (SAF DEG), which is the main acid hydrolysis product. The confirmation of degradation product build-up by the use of several analytical techniques, including infrared spectroscopy (IR), and mass spectrometry (MS) investigations. The present methodologies have been validated for linearity within the concentration range of 5–30 µg/ml for SAF, and 5–15 µg/mL, 2–15 µg/ml for SAF DEG for fourier self-deconvolution (FSD) and dual wavelength (DW) methods, respectively. The originality of these techniques lies in their status as the first stability-indicating spectrophotometric procedures that are both environmentally friendly. Moreover, the process of obtaining pure SAF DEG offers substantial economic benefits by obviating the need to acquire a costly constituent. The use of intelligent techniques was employed to analyze the pharmaceutical dosage form, potentially offering significant advantages to the pharmaceutical industry.